Shi'ism in the Islamic republic of Iran: it's Muslim world policy - Ra'ees, Wahabuddin Sahibuddin (ISTAC, 2015)
Religion and politics are closely linked in the Islamic Republic of Iran, especially its Muslim World policy. The Islamic Republic of Iran policies in Afghanistan, Iraq, Syria and the Republic of Yemen suggest that it promotes Shi’ite religious doctrinal values in its Muslim World policy. This study argues that the Islamic Republic has mainly provided political, diplomatic, economic, philanthropic and military assistance to the minority Shi’ite population of the Sunnite majority Muslim states with the aim, entailed in its 1979 revolution, of integrating the Shi’ite minority population of the Muslim states into the deep state or political processes coupled with a mission of ultimate control of the politics of the Muslim World. The Islamic Republic’s policies are purportedly going to bring about Muhammad Hassan al Mahdi’s return to the world to establish universal divine just political order. The Islamic Republic believes that the Sunnite majority Muslim states are the real threat to its grand design, and hence, undergirded by the principle of taqiyyah (dissimulation) it should cooperate with the West or any other state to achieve its mission and global interests and intentions.